Microbial colonization and degradation of marine microplastics in the plastisphere: A review - Zhai, Xinyi; Zhang, Xiao-Hua; Yu, Min (Frontiers in Microbiology, 2023)
Marine microplastic pollution is a growing problem for ecotoxicology that needs to be resolved. In particular, microplastics may be carriers of “dangerous hitchhikers”, i.e. pathogenic micro-organisms. Microplastics are colonized by bacteria, fungi, viruses, archaea, algae and protozoans, resulting in the biofilm referred to as the “plastisphere”. The microbial community composition of the plastisphere differs significantly from those of surrounding environments. Early dominant pioneer communities of the plastisphere belong to primary producers, including diatoms, cyanobacteria, green algae and bacterial members of the Gammaproteobacteria and Alphaproteobacteria. With time, the plastisphere mature, and the diversity of microbial communities increases quickly to include more abundant Bacteroidetes and Alphaproteobacteria than natural biofilms. Factors driving the plastisphere composition include environmental conditions and polymers, with the former having a much larger influence on the microbial community composition than polymers. Microorganisms of the plastisphere may play key roles in degradation of plastic in the oceans. Up to now, many bacterial species, especially Bacillus and Pseudomonas as well as some polyethylene degrading biocatalysts, have been showed to be capable of degrading microplastics. However, more relevant enzymes and metabolisms need to be identified. Here, we elucidate the potential roles of quorum sensing on the plastic research for the first time. Quorum sensing may well become a new research area to understand the plastisphere and promote microplastics degradation in the ocean.